Horus-Shed hunting in his chariot: An unpublished fragment in the Fitzwilliam Museum, Cambridge, E.GA.3137.1943 - Pietri, Renaud (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2022)
This article deals with a fragmentary relief now in the Fitzwilliam Museurn., Cambridge, E.GA.3137.1943, depicting the God Horus-Shed shooting arrows from his chariot, together with the God Bes driving the vehicle. Previously unnoticed, this fragment can be added to the corpus of a rare iconographical motive, the so-called "Holy Hunt of Horus-Shed in his chariot".